Types of Social Isolation and Their Social and Psychological Effects: Social Research - Natheerah Ibraheem Abdi; Muhammad Hussain Shwani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research deals with the subject of the types of social isolation and the social and psychological effects of each type. The importance of the research is reflected in the fact that isolation is one of the social phenomena in which the individual suffers from a deficiency in the quantity and quality of social relations with a sense of loneliness, and it is in the form of many types, and each type has social and psychological effects. This research aims to identify the types of social isolation and the social and psychological effects of each type, and in the end the research concluded that social isolation has several types, including isolation resulting from aging, isolation resulting from excessive use of the Internet, and isolation resulting from psychological diseases, in addition to Social isolation due to the Corona pandemic, and the research also found that the social effects of isolation are in depriving the individual from achieving personal identity and self-respect, social integration, receiving social support, weakness in social relationships, and leading to the emergence of violent behavior and family disintegration, while the psychological effects of isolation are depression, loneliness, addiction, anxiety, stress, feelings of inadequacy and other psychological effects that an individual may experience in society.